2021
DOI: 10.2196/24199
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Content of Idiopathic Pulmonary Fibrosis Groups and Pages on Facebook: Cross-sectional Analysis

Abstract: Background Patients use Facebook as a resource for medical information. We analyzed posts on idiopathic pulmonary fibrosis (IPF)-related Facebook groups and pages for the presence of guideline content, user engagement, and usefulness. Objective The objective of this study was to describe and analyze posts from Facebook groups and pages that primarily focus on IPF-related content. Methods Cross-sectional anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…There is a critical need to better understand the quality of information presented on social media platforms such as Twitter that are increasingly used by patients to both relay and receive information. Similar to what has been reported on other platforms ( 6 , 7 ), we found that Twitter frequently contains inaccurate and sometimes harmful information.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…There is a critical need to better understand the quality of information presented on social media platforms such as Twitter that are increasingly used by patients to both relay and receive information. Similar to what has been reported on other platforms ( 6 , 7 ), we found that Twitter frequently contains inaccurate and sometimes harmful information.…”
Section: Discussionsupporting
confidence: 88%
“…Inaccurate information was found in 7% of tweets, similar to the findings of a content analysis of posts regarding IPF on Facebook, which found that 5% of posts contained potentially harmful information ( 6 ). These results differ from another study by our group on information regarding IPF on YouTube, in which the frequency of videos recommending nonindicated therapies was 17% ( 7 ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast to hashtags, themed communities on websites such as Reddit represent posts related to exactly 1 topic of interest. Like hashtags, these communities, such as r/cripplingalcoholism , r/depression , or r/opiates Reddit subreddits and HIV Baidu Tieba bar, contain information that can target and understand behavioral health and disease [ 29 - 33 ]. In addition to hashtags and subreddits, some social media platforms allow for geotagging or sharing a user's geographical latitude and longitude coordinates in a post.…”
Section: Introductionmentioning
confidence: 99%